Protoplast-Based Regeneration Enables CRISPR/Cas9 Application in Two Temperate Japonica Rice Cultivars - Marion Barrera; Blanca Olmedo; Matías Narváez; Felipe Moenne-Locoz; Anett Rubio; Catalina Pérez; Karla Cordero-Lara; Humberto Prieto (Plants)
Rice (Oryza sativa L.), a staple food for over half of the global population, plays a pivotal role in food security. Among its two primary groups, japonica and indica, temperate japonica varieties are particularly valued for their high-quality grain and culinary uses. Although some of these varieties are adapted to cooler climates, they often suffer from reduced productivity or increased disease susceptibility when cultivated in warmer productive environments. These limitations underscore the need for breeding programs to incorporate biotechnological tools that can enhance the adaptability and resilience of the plants. However, New Genomic Techniques (NGTs), including CRISPR-Cas9, require robust in vitro systems, which are still underdeveloped for temperate japonica genotypes. In this study, we developed a reproducible and adaptable protocol for protoplast isolation and regeneration from the temperate japonica cultivars ‘Ónix’ and ‘Platino’ using somatic embryos as the starting tissue. Protoplasts were isolated via enzymatic digestion (1.5% Cellulase Onozuka R-10 and 0.75% Macerozyme R-10) in 0.6 M AA medium over 18–20 h at 28 °C. Regeneration was achieved through encapsulation in alginate beads and coculture with feeder extracts in 2N6 medium, leading to embryogenic callus formation within 35 days. Seedlings were regenerated in N6R and N6F media and acclimatized under greenhouse conditions within three months. The isolated protoplast quality displayed viability rates of 70–99% within 48 h and supported transient PEG-mediated transfection with GFP. Additionally, the transient expression of a gene editing CRISPR-Cas9 construct targeting the DROUGHT AND SALT TOLERANCE (OsDST) gene confirmed genome editing capability. This protocol offers a scalable and genotype-adaptable system for protoplast-based regeneration and gene editing in temperate japonica rice, supporting the application of NGTs in the breeding of cold-adapted cultivars.